Methodological aspects of innovation performance measurement in the IT sector = Metodologiczne aspekty pomiaru sprawności innowacyjnej w sektorze IT - Mazur, Karolina; Inków, Monika (Zielona Góra: Faculty of Economics and Management Press)
The aim of the paper is to answer the research question of what innovation performance indicators are appropriate for research on innovation process in the IT sector in the Lubuskie voivodship. The authors have used the method of systematic review of literature and have analysed 125 research papers and additional sources. The research consluions are that the indicators shoud consider such aspects as the dimmension of innovation performance, the type of product novelty and level of analysis.
Keywords: sprawność innowacyjna; metodyka badań; sektor IT; przegląd literatury; innovation performance; research methodology; IT sector; review of literature